Peran Manajemen Sumber Daya Manusia dalam Pemanfaatan Media Sosial Untuk Meningkatkan Penjualan UMKM Ibu PKK Desa Watesprojo, Kemlagi, Mojokerto - Ratna Agustina; Yusuf Rachman Al Hakim; Mochamad Irfan; Dwi Sembe Sigita; Setyaasih Setyaasih; Agus Sunaryo; Harjo Lukito (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service aims to increase the use of social media as a marketing and sales tool by FWEO Women MSMEs in Watesprojo Village, Mojokerto, through a human resource management approach. Initial situation analysis identified low utilization of digital platforms due to limited knowledge and skills. The Participatory Action Research (PAR) method or in human resource management is called participatory management which is implemented by involving FWEO Women in planning, intensive training on content creation, account management, and online marketing strategies, as well as ongoing mentoring. The results showed a significant increase in participant understanding and skills, the formation of collective social media accounts, and the development of collaboration between MSMEs. The emergence of local social media management groups and local leaders indicates internalization of knowledge and sustainability initiatives, in line with Social Cognitive Theory and transformational leadership. The conclusion confirms that the integration of human resource management principles in technology-based community empowerment is crucial for sustainable adoption and positive impact, recommending a comprehensive approach that focuses on holistic capacity development and the formation of community support structures.